The Role of Integrating Strategic Management Accounting with Big Data and Artificial Intelligence in Enhancing Financial Analysis and Decision-Making - Alimuddin, Alimuddin; Usman, Asri; Abbas, Aulia Thalita Sada; Fadila, Nuriya (Green Publisher Indonesia, 2025)
This study aims to systematically analyze the crucial role of integrating Strategic Management Accounting with Big Data and Artificial Intelligence (AI) in enhancing financial analysis capabilities and the effectiveness of strategic decision-making. Using the Systematic Literature Review (SLR) approach, this study synthesizes the findings of 29 relevant scientific articles indexed in the Scopus database from 2014 to 2024, identified through the keywords